Near-complete genome of cosavirus A from a child hospitalized with acute gastroenteritis, Brazil - Lobo, Patr?cia dos Santos (Elsevier, 2020)
Acute gastroenteritis (AG) is responsible for 525,000 deaths worldwide in children under-5-years and is caused by the Human Cosavirus (HCoSV; family Picornaviridae, Genus Cosavirus). Although its health importance, a significant percentage of diarrhea cases (? 40 %) still of unknown etiology. In Brazil, few studies have reported HCoSV-A sequences analyzing partial 5' UTR. This study characterized the first near-complete genome of a Cosavirus A (strain AM326) from a child hospitalized with AG in Amazonas state, Northern Brazil. High throughput sequencing (HTS) was performed using the HiSeq? 2500 platform (Illumina) in one fecal specimen collected from the Surveillance of Rotavirus Network of the Evandro Chagas Institute collected in 2017. Sequence reads were assembled by the De Novo approach using three distinct algorithmic (IDBA-UD, Spades, and MegaHit). The final contig was recovered from the HCoSV-AM326 sample revealing 7,735 nt in length (SRA number SRR12535029; GenBank MT023104) and the genetic characterization, as well as phylogenetic analysis demonstrated a new variant strain from Brazil, highlighting the association of HCoSV-A as a possible causative agent of AG. This finding demonstrates the importance of the metagenomic approach to elucidate cases of diarrhea without a defined etiology, as well as providing a better understanding about the virus genetics, evolution and epidemiology.